Persepsi Akseptor KB MOP dalam Penerapan Program KB di Kecamatan Gayamsari Kota Semarang - Anggy Dwi Putriandini (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2017)
Indonesia's fertility Rate is 2.6 and still be above the average TFR ASEAN countries, i.e. 2.4. In the Sub-District of Gayamsari did not escape the program policy KB, but men participants in this region is too little, until August 2014 man KB user use the MOP method only 76 people from 11.824 users of/PUS in the area, it means more or less the only 0.6% from total users in Gayamsari. The purpose of this study was to describe the application of Perception within the Program Aseptor KB MOP KB in district of Gayamsari, Semarang. This research uses descriptive qualitative approach to the subject of research as the main informant as much as 8 KB MOP aseptor in district of Gayamsari, as well as the triangulation PLKB informants in the region. Data collection is done with the interview in depth. The research results show the behavior of the application of the research KB MOP subjects is poorly because lack of the subject's self-awareness and motivation research even wearing it, not doing a follow-up counselling because being lazy and not interested, the subjects are not doing promotions to disseminate information about KB as embarrassed if many people know their participation as a aseptor, and roles PLKB Prio Utomo in the region who are not really supportive for the cause. The behavior of the subjects of the research are strongly influenced by their perception of the role of men in the KB program were knowledge, the perceived susceptibility, perceived seriousness, the perceived barriers, as well as the perceived benefits of the subject of research in the application of KB program in men.